THE EXPERIMENTAL STUDY ON STICKSLIP PROCESS OF BENDING FAULTS - Guo Yanshuang (Geodinamika i Tektonofizika, 2015)
The stickslip process of bending faults with one angle change of 5° at the connection location between the two line fault segments is investigated in this paper. The dynamic process and physical field evolution were observed in the laboratory, and measurements were recorded with application of fault displacement measurement, strain tensor analysis and acoustic emission (AE) techniques. The experimental results from the study of bending faults give grounds for the following primary conclusions: (1) It is clearly revealed that there is a negative correlation between the logarithms of the stickslip cycle and loading rate; (2) With different loading rates, most of the instabilities from bending faults occurred as earthquake doublets. It means that an instable event can contains two subevents which occur with an interval of time from 100 ms to 200 ms. (3) With application of different observation approaches, regardless of the fact that the sampling rates were the same, differences of the coseismic response were observed. For instance, strain measurements indicated significant strain weakening stage, but fault displacement was not significantly changed before fault instability. (4) Experimental studies of high sampling rates contribute to a better understanding and awareness of earthquake precursors and the seismogenic process; such studies are helpful in analyzing the mechanism of strong earthquake processes and parameters of aftershocks.